Anti‐cancer effect of N‐(3, 5‐bis(trifluoromethyl)phenyl)‐5‐chloro‐2, 3‐dihydronaphtho[1, 2‐b]furan‐2‐carboxamide, a novel synthetic compound. Issue 5 (11th April 2015) - Kwon, Sun Mi; Jung, Yu Yeon; Hwang, Chul Ju; Park, Mi Hee; Yoon, Na Young; Kim, Tae Myung; Yu, Ji Myung; Kim, Dae Hwan; Seo, Doo Won; Youn, Hyu Seok; Seo, Hyun Ok; Chung, In Sung; et al.
Abstract : Naphthofuran compounds have been known to regulate HNF 4α which is associated with proliferation, progression and metastasis of HCC. In this study, we investigated whether N‐(3, 5‐bis(trifluoromethyl)phenyl)‐5‐chloro‐2, 3‐dihydronaphtho[1, 2‐b]furan‐2‐carboxamide (NHDC), a novel synthetic naphthofuran compound inhibits liver tumor growth through activation of HNF 4α. Treatment with different concentrations (1–10.8 µM) of NHDC for various periods (0–72 h) inhibited liver cancer cells (HepG2, Hep3B) growth as well as colony formation followed by induction of apoptosis in a concentration dependent manner. NHDC also induced expression of the apoptosis regulating genes as well as inhibiting the action of STAT3. These inhibitory effects were associated with enhancement of expression and DNA binding activity of HNF 4α. In vivo study confirmed that liver tumor growth was prevented with NHDC (5 mg/kg), and its effect was also related with inhibition of STAT3 pathway through enhancement of expression and DNA binding activity of HNF 4α. Moreover, siRNA of HNF 4α abolished NHDC‐induced cell growth inhibition as well as DNA binding activity and phosphorylation of STAT3. Pull down assay docking prediction analysis proved that NHDC directly binds to hydrophobic fatty acid ligand binding site of HNF 4α. A novel naphthofuran compound, NHDC inhibited liver tumor growth by inactivating of STAT3 through direct biding to HNF 4α. © 2015 Wiley Periodicals, Inc.